Dexamethasone and granulocyte colony-stimulating factor affect the morphology of the perihematomal area in the brain of rats with local hemorrhagic stroke - Kuraieva , A.V.; Savosko , S.I. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Functional tests, morphological features of the perihematomal area, dynamics and intensity of migration of cells with a pro-inflammatory phenotype are considered to be the defining indicators for evaluating the effects of drugs on animal models of stroke. Objective. The purpose of the research was to investigate the dynamics of changes in the functional state of rats with a stroke and the migration of CD44+ cells into the perihematomal area after the administration of dexamethasone and granulocyte colony-stimulating factor. Methods. Unilateral hemorrhagic stroke was simulated in rats; dexamethasone, growth factor (rHuG-CSF) and their combination were injected subcutaneously on days 1, 2 and 3 of the experiments. The results of the "inverted screen test" and "platform test" were evaluated, the volume of the hematoma was measured morphometrically, CD44+ cells were detected immunohistochemically in the perihematomal area of the brain, and their migration activity was scored on a 3-point scale. Results. After simulating a stroke in rats, test results deteriorated sharply after 1 and 3 days, and partial recovery was observed after 10 days. The strength of the grasping reflex in the "inverted screen test" significantly decreased, and the time to perform the "platform test" increased. The results were characterized by the weak correlation between passing the "inverted test" and "platform test" and hematoma volume. Dexamethasone affected the development of cell reactions in the perihematomal area by delaying the migration of CD44+ cells and the elimination of blood cells by macrophages, and the growth factor promoted the infiltration of CD44+ cells in the first 3 days of the experiment. Conclusion. Functional tests made it possible to quantitatively assess the manifestations of neurological deficits (grasping reflex, forelimb strength) in animals that simulated a stroke without the appearance of limb paresis. CD44+ cell migration to the perihematomal area is potentially associated with remodeling of damaged brain tissue and hematoma elimination. The effect of dexamethasone was reflected in the delay in the recovery of limb function and the migration of CD44+ cells into the hemorrhage, while the growth factor contributed to the earlier appearance of CD44+ cells.